Seismic Performance Evaluation of a Reinforced Concrete Arch Bridge - Dangol, Jeena; Suwal, Rajan (Journal of the Institute of Engineering, 2017)
The entire Himalayan belt including Nepal area, because of its active tectonic movement, is seismically active causing high risk of earthquake in this region. It is important to evaluate the seismic performance of the structures including bridges to identify to what extent they would survive during earthquake. A reinforced concrete two hinged arch bridge located in Chobhar, Nepal has been selected for the research purpose. This paper presents the determination of seismic performance of a reinforced concrete arch bridge under different ground motions. The seismic input was taken as five different earthquake ground motion histories having different V/H peak ground acceleration ratio for time history analysis. Displacement capacity of the bridge was determined from pushover analysis. Time history analysis was conducted in two different steps: first only horizontal acceleration was applied and next vertical acceleration was applied in addition to horizontal ground motion. Comparisons were made between the responses of the bridge for these two cases. It was found that inclusion of vertical component of ground motion has negligible effect in variation of longitudinal displacement. However, there was remarkable effect in axial force variation. Significant effect in axial force variation in arch rib was observed as V/H ratio increased although the effect in longitudinal displacement with increase in V/H ratio was negligible. Moment demand also increased due to high axial force variation because of vertical ground motion. Journal of the Institute of Engineering, 2016, 12(1): 120-126